2009 IEEE International Workshop on Machine Learning for Signal Processing 2009
DOI: 10.1109/mlsp.2009.5306216
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative channel selection method for the recognition of anticipation related potentials from CCD estimated cortical activity

Abstract: Recognition of brain states and subject's intention from electroencephalogram (EEG) is a challenging problem for braincomputer interaction. Signals recorded from each of EEG electrodes represent noisy spatio-temporal overlapping of activity arising from very diverse brain regions. However, un-mixing methods such as Cortical Current Density (CCD) can be used for estimating activity of different brain regions. These methods not only improve spatial resolution but also signal to noise ratio, hence the classifiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A preliminary study on the feasibility of using CCD inverse solution for ERPs is reported in [7]. In our study, we found that the data from cortical sources not only increases classification accuracy for some subjects, but it also provides us an opportunity for neurophysiological interpretation of the ERP data in terms of active cortical sources.…”
Section: Introductionmentioning
confidence: 58%
“…A preliminary study on the feasibility of using CCD inverse solution for ERPs is reported in [7]. In our study, we found that the data from cortical sources not only increases classification accuracy for some subjects, but it also provides us an opportunity for neurophysiological interpretation of the ERP data in terms of active cortical sources.…”
Section: Introductionmentioning
confidence: 58%
“…We have previously explored its single trial recognition for BCI, designing methods for fast and online classification [22][23][24]. However, classification performance was largely varied across runs and subjects, sometimes staying at levels close to chance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it becomes more difficult to automatically find what information is useful in the available channels. Channel selection has been widely used in Brain Computer Interfaces [4][5][6][7][8][9][10] mainly for the purpose of computational load reduction. Constant (in time) importance of information captured by a channel can be assumed for these tasks, especially when classification systems targeted are patientspecific, that is, some representation of testing patient data is available beforehand [4], [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%